(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Nowadays, it cannot be denied that one of the problems students faces is specifically about finance, especially when a child comes from a low-income family. We chose this topic because we know that it is very significant, especially in the current situation during this pandemic. Many people are now suffering from different reasons, like financial, so we must pay attention to it. Some of them have lost their jobs, so this is the reason why we focused on the issue of financial problems that might affect the preferred careers of the students in the future. Each student’s career choice is one of the most important decisions; it decides the career path the individual wants to take. Students need to consider adapting their strengths and interests to their job choices. The reviewed studies provide evidence that a career development program requires and should have a collaborative effort made by the school administrator, teachers, and most guidance counsellors to concentrate on the decision in a student’s career. Research also indicates that when students feel the support and love of their parents, it influences the children’s career development and decision-making. The methods and design used in this study were qualitative and descriptive research. The instrument used to gather the data was the survey questionnaire and related literature and studies. The result of the study was based on the assessment made by the grade 12 HUMSS students on the Effects of Financial Problems on their career preferences. Financial problems influenced the students along with their academic performance and chosen careers in the future. Parents and teachers should prepare students for career awareness early, and parents must support their children, especially in their chosen careers. Based on the findings of this study, parents should work closely with their children in the career decision-making process, allowing students to choose from their interest areas. The income level of families with a child at high school may determine what career a student chooses during a specific time in that student’s life, choices that will determine a large part of the student’s future. Recommendations are: Setting your financial goals and budget, learning how to spend less and manage a budget, identifying top sources of financial stress, making the most of your income, and making adjustments as your income, spending and goals change.